Vanadium (V) bio-detoxification based on washing water of rice as microbial and carbon sources - Hao, Liting; Wang, Xinli; Shi, Jinkai; Li, Lin; Hao, Xiaodi (Frontiers in Environmental Science, 2023)
Mining and smelting result in vanadium (V) released into the environment. Biologically removing V(V) with washing water of rice (WWR) was investigated with this study. Over a 7-d trial, the V(V) removal efficiency increased with dosing WWR dosage, up to 56.6%. The results demonstrated that WWR could be used as carbon and microbial sources for biologically reducing V(V). Using domesticated sludge as inocula could enhance V(V) detoxification performance, and 95.5% of V(V) was removed in the inoculated system for 5 d. Soluble V(V) was transformed into insoluble V(IV) (VO2), which could be further removed with precipitation. Besides ABC transporters, two-component system was also involved in V(V) reduction. The study confirmed that WWR could be utilized for V(V) bio-detoxification.